Causas del congestionamiento vehicular en el centro histórico de la ciudad de Riobamba - Alarcón Vizuete, Bryan Vinicio (2023)
According to Valencia and Sanchez (2016) "The production or generation of solid waste is a variable that depends on cultural factors such as the size of the population, the dominant socioeconomic activity, the educational level and the environmental awareness that people have". Therefore, the physical characterization of household solid waste in the city of Macas and the people who generate it aims to generate data that will serve as a basis for the creation of environmental programs, promoting education and environmental awareness. Two phases were used to physically characterize household solid waste. Phase 1: General characterization of the urban population of the city of Macas, through the initial application of a survey conducted by Arellano, Gavilanes, & Gonzáles (2013) by the "Method of urban characterization and socioeconomic characterization" same that will allow to know the per capita production (PPC) of solid waste. Phase 2: Statistical analysis was used to characterize the solid waste produced by the inhabitants of the city of Macas. The process consisted of recording for eight days the amount of solid waste produced by the household, classifying, and weighing it according. To its physical composition to subsequently calculate the sample size and generate data on per capita production, loose density, components, among other tasks that are addressed in this report.